Regulating a pseudonym: Namibia's regulatory response to cross-border Cryptocurrency transactions - Ernstzen, Cedrine Veanca (Department of Commercial Law, 2021)
In 2008 the world witnessed a transformational shift in its financial services with the introduction and subsequent adoption of cryptocurrencies. The self-regulatory nature of cryptocurrencies is an attractive feature for its users. Unfortunately, this feature is equally as attractive for criminal use. It is for this reason that in 2018 the Financial Action Task Force amended its regulatory Recommendations to extend the obligations of anti-money laundering and combating the financing of terrorism to cryptocurrency service providers and users. In turn, jurisdictions such as the European Union have amended their anti-money laundering laws to give the Recommendations effect. However, cryptocurrency transactions are presently unregulated in Namibia, despite the country also being a member state of the Financial Action Task Force. Namibia's concerns surrounding cryptocurrencies are in no way limited to their ability to corrupt the integrity of its financial industry, but also their ability to evade Namibia's capital and exchange controls. These controls preserve Namibia's foreign reserves which can theoretically be under threat by pseudonymous cross-border cryptocurrency transactions. Consequently, the imminent threat which these transactions pose, in their current form void of regulation, can arguably be quantified by their lack of transparency, accountability, and their jurisdictional concerns. Notably, cryptocurrencies have the ability to lower the entry level for financial inclusion and have the potential to propel Namibia's economic growth if cultivated correctly. Therefore, this dissertation examines whether the licensing of cryptocurrency service providers within Namibia can remedy the ills that plague cross-border cryptocurrency transactions, in order to safeguard the integrity of Namibia's financial industry and ensure the preservation of its foreign reserves without stifling innovation.